Predictive modelling of tree species distributions on the Iberian Peninsula during the Last Glacial Maximum and Mid-Holocene - Benito Garzón, Marta; Sánchez de Dios, Rut; Sainz Ollero, Helios (Ecography, 2007)
This paper reports a bioclimatic envelope model study of the potential distribution of 19 tree species in the Iberian Peninsula during the Last Glacial Maximum (LGM; 21 000 yr BP) and the Mid-Holocene (6000 yr BP). Current patterns of tree species richness and distributions are believed to have been strongly influenced by the climate during these periods. The modelling employed novel machine learning techniques, and its accuracy was evaluated using a threshold-independent method. Two atmospheric general circulation models, UGAMP and ECHAM3 (generated by the Palaeoclimate Modelling Intercomparison Project, PMIP), were used to provide climate scenarios under which the distributions of the 19 tree species were modelled. The results obtained for these scenarios were assessed by agreement measure analysis; they differed significantly for the LGM, but were more similar for the Mid-Holocene. The results for the LGM support the inferred importance of pines in the Iberian Peninsula at this time, and the presence of evergreen Quercus in the south. Important differences in the altitude at which the modelled species grew were also predicted. During the LGM, some normally higher mountain species potentially became re-established in the foothills of the Pyrenees. The warm Mid-Holocene climate is clearly reflected in the predicted expansion of broad-leaved forests during this period, including the colonization of the northern part of the Iberian Peninsula by evergreen Quercus species.
Keywords: climate scenarios; iberian peninsula; Pinus; Quercus; refugia (voyant); species distribution modelling

Predictive modelling of tree species distributions on the Iberian Peninsula during the Last Glacial Maximum and Mid-Holocene - Benito Garzón, Marta; Sánchez de Dios, Rut; Sainz Ollero, Helios (Ecography, 2007)
This paper reports a bioclimatic envelope model study of the potential distribution of 19 tree species in the Iberian Peninsula during the Last Glacial Maximum (LGM; 21 000 yr BP) and the Mid-Holocene (6000 yr BP). Current patterns of tree species richness and distributions are believed to have been strongly influenced by the climate during these periods. The modelling employed novel machine learning techniques, and its accuracy was evaluated using a threshold-independent method. Two atmospheric general circulation models, UGAMP and ECHAM3 (generated by the Palaeoclimate Modelling Intercomparison Project, PMIP), were used to provide climate scenarios under which the distributions of the 19 tree species were modelled. The results obtained for these scenarios were assessed by agreement measure analysis; they differed significantly for the LGM, but were more similar for the Mid-Holocene. The results for the LGM support the inferred importance of pines in the Iberian Peninsula at this time, and the presence of evergreen Quercus in the south. Important differences in the altitude at which the modelled species grew were also predicted. During the LGM, some normally higher mountain species potentially became re-established in the foothills of the Pyrenees. The warm Mid-Holocene climate is clearly reflected in the predicted expansion of broad-leaved forests during this period, including the colonization of the northern part of the Iberian Peninsula by evergreen Quercus species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: climate scenarios; iberian peninsula; Pinus; Quercus; refugia (voyant); species distribution modelling

Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L (Tree Physiology, 2004)
Photoinhibition was examined in four co-occurring Mediterranean evergreen tree species during two consecutive winters. In response to low temperatures and saturating light, Juniperus phoenicea L., Pinus halepensis Mill., Quercus coccifera L. and Q. ilex ssp. ballota (Desf.) Samp. exhibited marked chronic photoinhibition, indicated by low predawn maximal photochemical efficiency of photosystem II (PSII) (Fv/Fm). Low Fv/Fm values were correlated with high concentrations of xanthophyll cycle components (VAZ) and with the maintenance of high concentrations of zeaxanthin overnight (DPSpd). In all species, however, chronic photoinhibition was enhanced as the winter progressed in the absence of changes in DPSpd, suggesting cumulative damage toward the end of winter.Photoinhibition differed among species: P. halepensis always displayed significantly higher Fv/Fm values; and Q. coccifera had the lowest Fv/Fm values, showing a high sensitivity to the combination of high light and low temperatures. Differences among species were not fully explained by differences in the xanthophyll pool or its de-epoxidation state. Chronic photoinhibition overlapped with a dynamic photoinhibition as shown by the low values of photochemical efficiency of the open reaction centers of PSII at midday. Winter photoprotective strategies differed among species and may involve photoprotective mechanisms in addition to those associated with xanthophylls. The observed species-specific differences matched results obtained for the same species in summer; however, comparison of the two seasons suggests that the higher VAZ concentration observed in winter has an additional structural photoprotective role.
From Duplicate 2 (Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L)
Keywords: chlorophyll; Chlorophyll: physiology; Juniperus; Juniperus: physiology; photoprotection; Pinus; Pinus: physiology; Plant Leaves; Plant Leaves: physiology; Quercus; Quercus: physiology; Seasons; Sunlight; Trees; Trees: physiology; xanthophyll cycle

An evaluation of the differences in the composition of humic acids in soils under oak and pine forest by GC-MS after mild degradation - González-Vila, F L; Almendros, G; Martin, F (Plant and soil, 1987)
Significant differences were found in the products released after eight samples of humic acids (HA's) isolated from soils under mediterranean pine and oak forests underwent mild degradation. A number of compounds, including typical degradation products of lignins, were found exclusively in the HA's from the soils under pine forests. The aliphatic constituents were more firmly retained in the HA's under oak, which presented mean values for aromatic acids lower than the humic samples from pine forests. Different types of diterpene resin acids were also found amongst the mild degradation products of HA's from the studied areas.
Keywords: Forest soils; humic acids; Lipids; mild degradation; Pinus; Quercus; resin acids